Analisi Sales Promotion dan E-Service Quality terhadap Customer Loyalty yang Dimediasi oleh Customer Satisfaction Pengguna Tokopedia di Kota Cimahi - Suci Nurahma Aztiannisa; Tania Adialita (Journal of Management and Bussines (JOMB), 2024)
This research aims to find out how sales promotions and electronic service quality influence customer loyalty through Tokopedia customer satisfaction in Cimahi City. The instruments used have been tested for reliability and validity. This instrument was used to collect data from 120 female respondents who were of productive age and had shopped on the Tokopedia application. Convenience sampling and cross-sectional time horizon are the two types of data collection used. The data processing method uses descriptive tests and multiple linear regression with SPSS version 23 and the Sobel test. The research results reveal that both sales promotions and electronic service quality positively affect customer satisfaction and customer loyalty, and customer satisfaction positively impacts customer loyalty. Furthermore, through customer satisfaction, sales promotions do not affect customer loyalty, while electronic service quality affects customer loyalty through customer satisfaction. Keywords: Sales Promotion, Electronic Service Quality, Consumer Satisfaction, Consumer Loyalty